PENGEMBANGAN BAHAN AJAR BERBASIS MODEL ORAL READING FLUENCY UNTUK MENINGKATKAN KEMAMPUAN MEMBACA LANCAR SISWA SEKOLAH DASAR DI KABUPATEN LIMA PULUH KOTA - Amelia Gusriani; Aminudin Zuhairi; Mutiara Felicita Amsal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is driven by the fact that learning activities in schools rely solely on student handbooks provided by the Ministry of Primary and Secondary Education. The researcher argues that supplementary books for students need to be developed using the Oral Reading Fluency learning model. Additionally, students' reading fluency skills are still lacking. This study aims to describe the development process of teaching materials based on the Oral Reading Fluency model that are valid, practical, and effective. This research was conducted with 30 second-grade students at Regional Technical Implementation Unit (UPTD) SD Negeri 02 Halaban, Lima Puluh Kota Regency. This study is a type of Research and Development (R&D) using the 4-D model, which consists of four stages: Define, Design, Develop, and Disseminate.Validity data were obtained through teaching material validation sheets, the implementation of lesson plans, and teacher and student response assessments. Effectiveness was measured based on the students' reading ability outcomes. The results of the development research show that the teaching materials were first validated by expert validators and educational practitioners to obtain feedback, resulting in materials that align with the Oral Reading Fluency model to help students improve learning quality. Consequently, the developed materials fall into the